2019
DOI: 10.1177/0363546519850578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Meniscal Regeneration in a Mini Pig Model Treated With a Novel Polyglycolic Acid Meniscal Scaffold

Abstract: Background: Meniscal injury is a severe impediment to movement and results in accelerated deterioration of the knee joint. Purpose: To evaluate the effect of a novel meniscal scaffold prepared from polyglycolic acid coated with polylactic acid/caprolactone on the treatment of meniscal injury in a mini pig model. Study Design: Controlled laboratory study. Methods: The model was established with a 10-mm resection at the anterior medial meniscus on both knee joints. A scaffold was implanted in the right knee join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…28 Our previous meniscus studies showed hat PGA induces cell proliferation within 4 weeks after implantation. 21,29 In the current study, cell viability assay showed that a large number of cells survived in the MSS group for 2-4 weeks. Based on these results, we expected that a two-layer scaffold consisting of PGA in contact with the meniscus surface and P(LA/CL) in contact with the cartilage surface might be a good combination.…”
Section: Discussionsupporting
confidence: 48%
“…28 Our previous meniscus studies showed hat PGA induces cell proliferation within 4 weeks after implantation. 21,29 In the current study, cell viability assay showed that a large number of cells survived in the MSS group for 2-4 weeks. Based on these results, we expected that a two-layer scaffold consisting of PGA in contact with the meniscus surface and P(LA/CL) in contact with the cartilage surface might be a good combination.…”
Section: Discussionsupporting
confidence: 48%
“…The results showed that the scaffold provided appropriate initial strength and could prevent cartilage degeneration with relatively low inflammation. However, the compressive stress and elastic modulus of the scaffold were significantly inferior to those of the native meniscus ( Otsuki et al, 2019 ).…”
Section: Polymers For Meniscal Tissue Engineering Applicationsmentioning
confidence: 87%
“…As a biodegradable polymer with excellent biocompatibility and mechanical strength, poly(glycolic acid) (PGA) has been widely used in the biomechanical and medical fields since the 1970s and can serve as a scaffolding material to repair articular cartilage in clinical practice ( Siclari et al, 2018 ; Otsuki et al, 2019 ; Cojocaru et al, 2020 ). In meniscal tissue engineering, a 3D, meniscal-like, PGA-hyaluronan implant with high porosity was developed, and this scaffold showed high biocompatibility and improved the expression of chondrogenic genes during coculture with human meniscal cells in vitro .…”
Section: Polymers For Meniscal Tissue Engineering Applicationsmentioning
confidence: 99%
“…12 Similarly, several researchers are performing in vivo meniscus and articular cartilage repair in the minipig. [60][61][62] Here, constructs were generated from the costal cartilage of the Yucatan minipig and stimulated during the maturation stage. Similar to constructs derived from bovine articular chondrocytes, compressive stiffness and tensile strength and stiffness of minipig-derived neocartilage significantly increased by 46%, 78%, and 78%, respectively, when FIS stress was applied.…”
Section: Discussionmentioning
confidence: 99%